Central metabolite and sterol profiling divides tobacco male gametophyte development and pollen tube growth into eight metabolic phases. (11th August 2017) - Rotsch, Alexander H.; Kopka, Joachim; Feussner, Ivo; Ischebeck, Till
Summary: While changes in the transcriptome and proteome of developing pollen have been investigated in tobacco and other species, the metabolic consequences remain rather unclear. Here, a broad range of metabolites was investigated in close succession of developmental stages. Thirteen stages of tobacco male gametophyte development were collected, ranging from tetrads to pollen tubes. Subsequently, the central metabolome and sterol composition were analyzed by GC‐mass spectrometry (MS), monitoring 77 metabolites and 29 non‐identified analytes. The overall results showed that development and tube growth could be divided into eight metabolic phases with the phase including mitosis I being most distinct. During maturation, compounds such as sucrose and proline accumulated. These were degraded after rehydration, while γ‐aminobutyrate transiently increased, possibly deriving from proline breakdown. Sterol analysis revealed that tetrads harbor similar sterols as leaves, but throughout maturation unusual sterols increased. Lastly, two further sterols exclusively accumulated in pollen tubes. This study allows a deeper look into metabolic changes during the development of a quasi‐single cell type. Metabolites accumulating during maturation might accelerate pollen germination and tube growth, protect from desiccation, and feed pollinators. Future studies of the underlying processes orchestrating the changes in metabolite levels might give valuable insights into cellular regulation of plant metabolism. Significance Statement: This study presents a primary metabolite map of 13 developmental stages of tobacco male gametophytes ranging from tetrads to mature pollen, rehydrated pollen and pollen tubes. The close succession of the monitored developmental stages demonstrated that the metabolite pattern changes sharply several times, especially during mitosis I and during rehydration.